Mobile Commerce and Consumers’ Online Purchase Orientation in Poland, Croatia and Serbia (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
As an innovative approach to retail, mobile commerce develops rapidly during last decade. It brings new challenges and opportunities in front of retailers who have to adapt their business strategies to new generation shoppers. With a good understanding of the shoppers’ online purchase intention, retailers are able to develop effective online strategies to attract new and keep loyal web-shopping customers. The purpose of this paper is to explain the online shopping orientation in the context of country of origin. There is a limited number of such research in Central and Eastern Europe, so there is a lack of knowledge about young consumers from this region and their attitude as mobile technology users. The article is based on the research conducted in Poland, Croatia and Serbia where 454 young non randomly selected respondents answered online survey questions. The research hypotheses were tested using correlation and non-parametric statistics. Differences between observed countries suggest that there is a necessity to adapt approach concerning online retailing even at the market with similar characteristics. Therefore, creators of marketing and sales strategies of online and omnichannel companies should consider this fact when planning business strategies.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.